Apparent temperature and heat-related illnesses during international athletic championships: A prospective cohort study - Hollander, K.; Klöwer, M.; Richardson, A.; Navarro, L.; Racinais, S.; Scheer, V.; Murray, A.; Branco, P.; Timpka, T.; Junge, A.; Edouard, P. (Scandinavian Journal of Medicine & Science in Sports, 2021)
International outdoor athletics championships are typically hosted during the summer season, frequently in hot and humid climatic conditions. Therefore, we analyzed the association between apparent temperature and heat-related illnesses occurrence during international outdoor athletics championships and compared its incidence rates between athletics disciplines. Heat-related illnesses were selected from illness data prospectively collected at seven international outdoor athletics championships between 2009 and 2018 using a standardized methodology. The Universal Thermal Climate Index (UTCI) was calculated as a measure of the apparent temperature based on weather data for each day of the championships. Heat-related illness numbers and (daily) incidence rates were calculated and analyzed in relation to the daily maximum UTCI temperature and between disciplines. During 50 championships days with UTCI temperatures between 15°C and 37 °C, 132 heat-related illnesses were recorded. Average incidence rate of heat-related illnesses was 11.7 (95%CI 9.7 to 13.7) per 1000 registered athletes. The expected daily incidence rate of heat-related illnesses increased significantly with UTCI temperature (0.12 more illnesses per 1000 registered athletes/°C; 95%CI 0.08-0.16) and was found to double from 25 to 35°C UTCI. Race walkers (RR = 45.5, 95%CI 21.6-96.0) and marathon runners (RR = 47.7, 95%CI 23.0-98.8) had higher heat-related illness rates than athletes competing in short-duration disciplines. Higher UTCI temperatures were associated with more heat-related illnesses, with marathon and race walking athletes having higher risk than athletes competing in short-duration disciplines. Heat-related illness prevention strategies should predominantly focus on marathon and race walking events of outdoor athletics championships when high temperatures are forecast.